SOME BRUCHIDS AND THEIR HOSTS IN THE ENVIRONS OF DELHI - VERMA, B. R.; LAL, B. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 1987)
Among the bruchids; Bruchidius species, which emerged from Acacia catechu seeds, is new species ever recorded, is being described separately elsewhere, adding another, species infesting A catechu seeds. Other bruchids-Bruchidius nalandus (Pic.), B. Sahelicus Decelle, B. Sparsenaclaus (Pic.) and Caryedon serratus palaesticus Southgate, emerged from seeds of Tephrosia purpurea Pers, Dichrostachys cinerea Wight and Arn, Albizia lebbek Benth and Acacia leucophloea Willd, respectively, presented new host records for these bruchids.